PENGARUH KUALITAS PRODUK, PERSEPSI HARGA DAN DIGITAL MARKETING TERHADAP KEPUASAN PELANGGAN DI PIZZA MARZANO PONDOK INDAH MALL 2 - Achmad Fadjri; Parlagutan Silitonga (LPPM and Travel Operation Department Universitas Asa Indonesia, 2019)
This research aims is to analyze the impact of product quality price perception and digital marketing. The research done in Restaurant Pizza Marzano Pondok Indah Mall 2, South Jakarta, as many as 200 respondents. Methode used is multiple regression . Based on the analysis, it can be concluded that, there is a real effect of product quality variables to the customer satisfaction with a contribution of 3,42%. There is a real influence of bundling price variable to customer satisfaction with contribution equal to 13,69%. There is a real influence of digital marketing variable to customer satisfaction with contribution equal to 16%. If the variables are combined together it is found that there is a concrete influence of the three variables together to determine the customer satisfaction with a contribution of 45,83%, where other factors are influential but not discussed in this research that is equal to 54.17%.